Evidence-based practices in teaching - Eliza Rybska; Renata Dudziak; Pascal Pollmeier (Problemy Wczesnej Edukacji)
This article presents the results of the implementation of the Erasmus Plus project (KA203 financed by the European Union, contract number 2019-1-NL01-KA203-060339) Research in Teacher Education (RiTE). The aim of the project was to promote and facilitate pre-service teachers to create and undertake evidence-based practices in teaching science, technology, engineering, and mathematics (STEM). In the RiTE project, pre-service teachers were encouraged to use evidence from educational and scientific research and to experiment and introduce didactic innovations in teaching and learning processes. Although it has its justification in the tradition of thinking about science, evidence-based practice is not yet consciously applied in school practice. In the article, we present both the theoretical framework for such practices, and the results of qualitative research – an analysis of interviews conducted with students, future teachers, and novice teachers involved in the project. The presented results show changes in the context of an understanding of evidence and what evidence-based practices are in the teaching process and the vision of such teaching presented by the respondents.